Limited Fine Motor and Grasping Skills in 6‐Month‐Old Infants at High Risk for Autism. Issue 6 (30th June 2014) - Libertus, Klaus; Sheperd, Kelly A.; Ross, Samuel W.; Landa, Rebecca J.
<x xml:space="preserve">Abstract</x> Atypical motor behaviors are common among children with autism spectrum disorders (ASD). However, little is known about onset and functional implications of differences in early motor development among infants later diagnosed with ASD. Two prospective experiments were conducted to investigate motor skills among 6‐month‐olds at increased risk (high risk) for ASD (N1 = 129; N2 = 46). Infants were assessed using the Mullen Scales of Early Learning (MSEL) and during toy play. Across both experiments, high‐risk infants exhibited less mature object manipulation in a highly structured (MSEL) context and reduced grasping activity in an unstructured (free‐play) context than infants with no family history of ASD. Longitudinal assessments suggest that between 6 and 10 months, grasping activity increases in high‐risk infants.